The reality of the cognitive burden of the methods of teaching physical education for male and female teachers of Al-Karkh Al-Thania Education Directorate - Fatima Naeem (physical education and sport sciences college for women/ Baghdad University, 2021)
The aim of the research is to build a cognitive load scale for the methods of teaching physical education for male and female teachers of the eduction for male and female teachers of the second karkh Education Directorate , and to identify the details of the leval of cognitive burden for the methods of teaching physical education forthem . Baghdad Al - Karkh /2 numbering (59) individuals , all of them were chosen deliberately at a rate of (100%) , and then they wrer divded into three samples ( contruction , exploratory and application ) according to the requirements of the research , and a specialized cognitive burden scale was  built for the sample and the specificity of this The research is according to the determinants of measurement and evaluation , and its application in apaper form with direct measurement , as the time prtiod for procedures and application took from 5l1l2021 to 28l2l2021 and after data was obtained , it was processed using the (SPSS) system  to be the only extracts and applicatons from this research in that Teachers of physical education in middle school need to schedule and properly codify the information the receive about how to evaluate , and the need to rely on official sources about virtual classroom information and e-learning  by reducing its momentum on their minds , and it is necessary that continuous development courses have reakistic goals and do not cause a cognitive burden . and exhausting them, and it is necessary to find open channels of communication to help them identify useful inforomation from non- improvised scintific sources